Genetic diversity analysis of coconut eriophyid mite (Aceria guerreronis Keifer) (Acari: Eriophyidae) population based on inter simple sequence repeat (ISSR) markers - J. Sathiya Prakash; K. Ramaraju; P. Meenakshisundaram; M. Maheswaran (International Coconut Community, 2007)
DNA markers have been employed on several insect species to estimate the genetic diversity across their populations. In the present study, an attempt was made to survey the extent of diversity among the coconut eriophyid mite [Aceria guerreronis Keifer Eriophyidae: Acari] populations collected from various ecological zones of Tamil Nadu, India. A total of 13 samples of eriophyid mite were analyzed by using 5 inter simple sequence repeat (ISSR) primers. The number of scorable markers produced by an individual primer ranged from 3-20 with an average of 10.6 markers per primer. Out of 53 markers generated with 5 ISSR primers, 11 were polymorphic across the 13 mite samples with an overall polymorphism of 20.75%. The lowest and the highest level of polymorphism were observed with primers viz. ISSR02 (30.76%) and ISSR01 (100%), respectively. The data matrix obtained for the presence or absence of markers across the 13 mite populations was analyzed to estimate the genetic distance between each sample. The analysis indicated that the mite populations collected from different locations are almost similar, genetically.